2018
DOI: 10.1089/ten.tea.2018.0036
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Biochemical Effects of Progesterone on Engineered Cervical Tissue

Abstract: Preterm birth is a leading cause of morbidity and mortality in newborns. Babies born prematurely are at increased risk of lifelong health problems, including neurodevelopmental abnormalities. Cervical shortening precedes preterm birth in many women. Cervical shortening is caused, in part, by excessive softening of the extracellular matrix (ECM) of the cervical stroma. In clinical obstetrics, cervical shortening prompts treatment with supplemental progesterone to prevent preterm birth. However, progesterone-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…stretch or stress), identifying particular homeostatic state(s) cells work to maintain, and understanding how pregnancyinduced changes in biological and mechanical cues combine to affect intracellular signalling and alter gene expression and/or protein production. In vitro studies using three-dimensional cervical stromal cell culture systems [94] will provide a useful platform to study how mechanics, along with cellular signals, drive cervicalcell specific functions to achieve the dynamic and multi-factorial changes required in cervical remodelling.…”
Section: Future Directionsmentioning
confidence: 99%
“…stretch or stress), identifying particular homeostatic state(s) cells work to maintain, and understanding how pregnancyinduced changes in biological and mechanical cues combine to affect intracellular signalling and alter gene expression and/or protein production. In vitro studies using three-dimensional cervical stromal cell culture systems [94] will provide a useful platform to study how mechanics, along with cellular signals, drive cervicalcell specific functions to achieve the dynamic and multi-factorial changes required in cervical remodelling.…”
Section: Future Directionsmentioning
confidence: 99%
“…To address the limitations of current models of cervical softening during pregnancy, engineered models of cervical tissue are being investigated [133]. During pregnancy, it is known that cervical tissue is exposed to multiple factors that could decrease cervical stiffness including changes in hormone concentrations, inflammatory conditions, and mechanical loading.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…After 4 weeks, the seeded scaffolds produced an ECM with biochemical components and histological appearance similar to native cervical stroma. Using the engineered cervix model, the influence of steroid hormones on ECM properties was studied [133]. The engineered cervix model suggested estradiol promoted ECM growth and progesterone had a softening effect.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…2D). 110 3D in vitro models of this tissue have been used to evaluate cell-ECM interactions. Mechanical and biochemical effects of progesterone on cervical tissue were…”
Section: Cervical Tissuementioning
confidence: 99%
“…By measuring collagen content and crosslinking in the scaffolds after stimulation with progesterone, they demonstrated that fibroblasts changed their morphology and decreased their production of collagen, leading to a decrease in cervical tissue stiffness. 110 An in vitro model commonly used to study skin has also been employed to study cervical cancer: organotypic raft cultures. Organotypic raft cultures are multilayered models of collagen, fibroblasts, and keratinocytes that are maintained at an air-liquid interface.…”
Section: Reviewmentioning
confidence: 99%